PERUMUSAN STRATEGI PENGEMBANGAN PRODUK KURMA SALAK BERDASARKAN ANALISIS PRODUCT LIFE CYCLE (PLC) DAN SWOT PADA KELOMPOK TANI AMBUDI MAKMUR II - Fitri Agustina; Nuzullis Lailatul Kamalia (Asian Journal of Innovation and Entrepreneurship, 2012)
Product development is necessary for companies to be able to survive in an increasingly turbulent business environment. This study aims to (1) to formulate an alternative strategy product development kurma salak based on product life cycle analysis and SWOT (2) choose an alternative strategy that prioritized for implementation. In this research which become sample is Kelompok Tani Ambudi Makmur II in district Bangkalan that produce food and beverages processed from Salak especially kurma salak that becomes Bangkalan flagship product. The method usedis the SWOT matrix, Product Life Cycle (PLC) and QSPM matrix. Technique analyse used by data is descriptive analysis technique. Conclusion from research show there are ten alternative strategies which is then sorted by total value of attractive scores. Three alternative strategies with the greatest Total Attractive Score (TAS) is expanding its marketing area, to develop production sites in other areas, increasing the production of kurma salak. Keywords: product development strategy, PLC, SWOT